Peranan Advokat sebagai Pemberi Bantuan Hukum dalam Menentukan Strategi Penyelesaian Perkara - Sasra, Adelia Dara; Kharismawati, Alfaning Martina; Hibahtillah, Muhammad Alldo; Ritiau, Ester Joytry; Sumardiana, Benny; Abidah, Shofriya Qonitatin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Factors influencing the effectiveness of advocates’ role as legal aid providers in determining case resolution strategies. Advocates play a crucial role in the legal system, particularly in providing appropriate legal assistance and solutions for clients. However, their effectiveness is influenced by various factors, such as the advocate’s competence, understanding of the case, access to legal resources, and the dynamics of relationships with clients and law enforcement officials. Through a qualitative approach, this study identifies these factors and their implications for case resolution strategies. The research findings are expected to provide recommendations for improving the quality of legal aid in Indonesia.